A Crisis of Confidence: The Case of Dengvaxia in the Philippines - Mendoza, Ronald U (Archīum Ateneo, 2020)
At the time of publishing this case, a “health crisis of confidence” was gripping the Dengvaxia (dengue vaccine) immunization program in the Philippines. The series of events that led to this could be traced back at least to late 2017, when some government officials under the then newly installed Duterte administration along with a group of stakeholders began to publicly raise issues as to the health impact of the vaccine — with some raising alarms in media that the vaccine directly led to the deaths of children. This case tackles the governance issues surrounding this program, emphasizing the important role of public communication. As there indeed were governance issues surrounding a vaccine program, how best to address them given the potential public health implications? The primary sources of information for this case are key informant interviews with former officials of the Department of Health (DOH). Secondary sources are government-issued documents and statistics, media reports, and journal articles. This case outlines the full timeline of the Dengvaxia crisis, including key events such as: (a) The announcement of Sanofi, the vaccine manufacturer, on November 2017 that Dengvaxia may increase the risk of severe dengue for those who haven't had dengue in the past, which led to a cascade of events leading to the suspension of the dengvaxia program; (b) the spread of false news by well-known individuals in both government and mass media claiming that the vaccine directly caused the deaths of children; (c) the statements of the DOH that criticized Sanofi and Dengvaxia, which reinforced the claim on the vaccine’s ineffectiveness; (d) and the widely publicized and dramatized investigation of the issue, which was widely covered by media in the country and abroad. The politicization of the supposedly scientific issue not only damaged the credibility of the dengue vaccine but also the long-established programs of the DOH, such as the measles immunization program. How could this “health crisis of confidence” have been averted or managed differently? How did the chain of events set up the Dengvaxia program for its controversial fate? How could public information have been managed differently by the various actors?